The modelling of corrective surface for gps height conversion in klang valley - Khalid, Abza (Faculty of Geoinformation and Real Estate, Universiti Teknologi Malaysia, 2011)
The modern technique in GPS-levelling plays a tremendous role of importance and alternative for practical height determination. One of the GPS-levelling contributions utilized is able to provide height information quickly. However, height given by GPS (h) has to be transformed to orthometric height (H) in order to use for the survey. In this case, the existence of the geoid undulation (N) is much needed and appreciated to allow the conversion processes occur. Although the theoretical relationships between these height types are simple in nature, practically are quite challenging due to numerous factors that cause discrepancies among the combined height data. This study focused on modelling the corrective surface in the form of geometric geoid for GPS height conversion in Klang Valley. Therefore, the relationship between h, H and N at 42 co-location points around Klang Valley was investigated in order to derive the corrective surface. Then, the method of least square adjustment (LSA) is used to determine the right parameter for corrective surface computation. Software will be developed to get the GPS conversion factor for Klang Valley. Analysis shows that the 4-parameter of simplified transformation model is the best parametric fit in Klang Valley area with Standard Deviation of 0.0215m and RMS of 0.0023m after fitting. Software named ‘KLANG VALLEY Corrective Surface v1.0’ is developed by using Microsoft Visual Basic v6 to get the GPS conversion factor for Klang Valley